ANALISIS PRODUKTIVITAS, PENDAPATAN, DAN KESEJAHTERAAN PETANI KARET EKS UPP TCSDP DI DESA GUMANTI KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Khairunas '; Jum’atri Yusri; Ahmad Rifai (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to analyze the productivity, to analyze the revenue, to analyze of the households income structure, to analyze the pattern of households expenditure, and to analyze the welfare of households of the smallholder rubber plantation of ex-TCSDP development. Research was done by survey at Gumanti Village. Analyzing the structure of household expenditure Ex-UPP rubber farmers in the village TCSDP Gumanti District of Peranap, Analyzing household welfare level of Ex-UPP rubber farmers in the village TCSDP Gumanti District of Peranap. This Research with survey method and sampling of 30 samples. Analysis of the results showed that the productivity of smallholder rubber plantation as 3.047 ton/ha/year, equivalent in the form of revenue latex and rubber plantations ex TCSDP Rp. 902 977 / pc / month. The structure of household income derived from agriculture is 51.08 percent and 48.92 percent for non-agricultural income. The pattern of household expenditure shown that the food expenditure as 41.15  percent and non-food expenditures as 58.85 percent. Result also show that the household of the smallholder rubber plantation at Gumanti Village have the total expenditure more than 240 kg of rice equivalent. The level of household welfare rubber farmers in the village Gumanti in absolute poverty approach is at peace tingkar where income per capita per month is greater than the poverty line Indragiri Hulu and the relative poverty approach is based on 14 indicators of fulfillment of basic needs of 58.85 percent are in prosperous category that fulfill 1-3 indicators of poor condition and the rest are in the category of most prosperous that fulfill 4-8 indicator of poor conditions at 46.67 percent. Key words : Rubber Farmer, Productivity, Income, Outcome, Welfar